The Interaction between Adding Soybean Residue and Hydrogel to the Soil on the Mineral Content of Yellow Corn (Zea mays L.) Plants whose Seeds are Treated with Ascorbic Acid - Yasir Mahmood; Mohammad Faysail (College of Education for Pure Sciences, 2024)
This study was conducted in the warehouse of the Department of Biology / College of Education for Pure Sciences for the 2023-2024 season to study the effect of adding levels of hydrogel (0, 2, 4) gm/kg of soil and residues of the vegetative part of soybeans at levels (0, 4, 8) gm/kg soil in the mineral content of yellow corn plants soaked with concentrations of (0,100, 200 ppm) of ascorbic acid. The results were analyzed using a completely randomized design and a factorial experiment with three replications. The results confirmed the existence of a discrepancy in the effect of soybean residues on mineral elements, as they ranged between inhibition and stimulation, as the residues had a stimulating effect on the calcium and nitrogen elements, While its effect was inhibitory to the element sodium and magnesium, and the addition of hydrogel showed a stimulating effect in all the nutritional elements mentioned above. On the other hand, there was a significant superiority in the content of the elements with an increase in the concentration of ascorbic acid compared to the control treatment without addition. The interactions showed a stimulating effect, especially the interaction of hydrogel levels with ascorbic acid concentrations in the studied characteristics